Determination of filtration and consolidation properties of protein crystal suspensions using analytical photocentrifuges with low volume samples. (16th March 2019) - Radel, B.; Funck, M.; Nguyen, T.H.; Nirschl, H.
Highlights: Analysis of key filtration parameters with just 200–500 μL sample per experiment. Crystal breakage at low pressures during the centrifugal filtration. Specific resistance and compressibility are strongly dependent on crystal shape. Abstract: Proteins and in particular pharmaceutical proteins like monoclonal antibodies are expensive products. Protein crystallization is an interesting alternative process step to the common purification and formulation of such proteins. The solid-liquid separation of proteins however, is a challenging task because the proteins are sensitive to mechanical stress, which could lead to crystal breakage and often are only available in small amounts for research and development. In this study a newly developed filtration cell for the LUMiSizer® centrifuge is used to analyze the filtration behavior with low volume samples. Isometric and needle shaped lysozyme crystals serve as model protein crystals. The needle shaped crystals showed about twice as high compressibility and much higher cake resistance than the isometric lysozyme crystals. After the filtration at maximum pressure in the centrifuge the mean particle diameter decreased compared to the unstressed median diameter. With the filtration cell the cake height and filter cake compression can be monitored in situ and the filter cake resistance and solids volume fraction can be calculated with one experiment using 200–300 μl sample.